Pengaruh Kompetensi, Komunikasi Dan Kompensasi Terhadap Kinerja Karyawan Perusahaan Di Kecamatan Jagakarsa Jakarta Selatan - Safa Putri Nurfitrialin; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Bintang Manajemen, 2024)
This research aims to analyze and determine the influence of competence, communication and compensation on employee performance in a company. This research was conducted using a quantitative approach and involved respondents consisting of employees at various levels of positions who work at companies in the district. Jagakarsa, South Jakarta. Data was collected through a questionnaire with a total of 22 questions and a total of 100 respondents which could measure the level of competency, communication, compensation and employee performance. The data analysis technique used in this research is SEM PLS (Structural Equation Modeling - Partial Least Squares), which was carried out using SmartPLS 4.0 software. The data analysis methods used in this research include measurement model analysis, structural model analysis, and direct influence hypothesis testing. The results of data analysis show that employee competency has a significant positive influence on employee performance. Communication also has a significant positive influence on employee performance. Effective and open communication allows clear and timely information to have a positive and significant impact on improving employee performance. And the compensation variable was also found to have a significant positive influence on employee performance. These findings provide important implications for human resource management and organizational practitioners in designing policies and programs related to competency development, improving communication, and providing adequate compensation for employees so that employees can provide reciprocity in the form of maximum performance for the company.